2012
DOI: 10.1007/s00705-012-1478-5
|View full text |Cite
|
Sign up to set email alerts
|

Genetic characterization of bovine viral diarrhoea (BVD) viruses: confirmation of the presence of BVD genotype 2 in Africa

Abstract: Bovine viral diarrhoea virus (BVDV) has emerged as one of the economically important pathogens in cattle populations with a worldwide distribution causing a complex of disease syndromes. Two genotypes BVDV 1 and 2 exist and are discriminated on the basis of the sequence of the 5′ non-coding region (5 NCR) using real-time PCR. The use of the real-time PCR is more sensitive, specific, and less time consuming than a conventional PCR, and has reduced the risk of cross-contamination of samples. Limited information … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 28 publications
1
5
0
Order By: Relevance
“…The variation may reflect to some extent the importance and scale of cattle keeping in these areas compared to Asia and possibly the lower seroprevalence may be down to a lower cattle density in some parts of Asia. These estimates are similar to the others reported in the literature ( 12 , 13 , 66 ). Despite the range of seroprevalence across geographies, the overall high seroprevalence reported across LMICs suggests that there are likely inefficiencies in livestock production across these regions ( 4 , 67 ).…”
Section: Discussionsupporting
confidence: 92%
“…The variation may reflect to some extent the importance and scale of cattle keeping in these areas compared to Asia and possibly the lower seroprevalence may be down to a lower cattle density in some parts of Asia. These estimates are similar to the others reported in the literature ( 12 , 13 , 66 ). Despite the range of seroprevalence across geographies, the overall high seroprevalence reported across LMICs suggests that there are likely inefficiencies in livestock production across these regions ( 4 , 67 ).…”
Section: Discussionsupporting
confidence: 92%
“…BVDV‐2 showed a high frequency in this study, which is demonstrated by the large number of BVDV‐2b strains that were isolated; in contrast, BVDV‐2a strains were not detected. The prevalence of BVDV‐2 was higher than what has been described in most of countries, where the frequency of this species is usually low (Mahony et al., ; Ridpath et al., ; Booth et al., ; Ularamu et al., ; Luzzago et al., ; Pecora et al., ; Zhang et al., ). The high frequency of BVDV‐2 was similar to what has been previously described in Brazil (Bianchi et al., ; Weber et al., ), in Chile (Pizarro‐Lucero et al., ) and in South Korea (Oem et al., ), although the latter two countries are known to have lower numbers of BVDV‐2b strains.…”
Section: Discussionmentioning
confidence: 74%
“…In this study, amplicon obtained from two PCRs was sequenced, and found to belong to the BVDV-1 genotype, which according to previous studies is more common in Africa than BVDV-2 (Baule et al 1997; Emran et al 2014; Kabongo, Baule & Van Vuuren 2003; Thabti et al 2005; Ularamu et al 2013; Van Vuuren 2005; Vilcek et al 2000; Yesilbag et al 2017). For example, in 2013, 82.5% of samples obtained from feedlots in various parts of South Africa and Namibia belonged to BVDV-1, and 17.5% to BVDV-2 (Ularamu et al 2013). The two isolates sequenced in this study were identical to each other, which is not surprising, given the fact that they originated from animals in the same herd.…”
Section: Discussionmentioning
confidence: 71%
“…Several prevalence studies have been conducted in southern Africa. In South Africa, prevalences ranging from 37% to 100% in cattle have been detected (Ferreira, Lourens & Van Vuuren 2000; Njiro et al 2011; Ularamu et al 2013). In a Namibian study in the late 1980s, 49% of cattle, 9% of sheep and 5% of goats had neutralising antibodies to BVDV (Depner, Hubschle & Liess 1991b).…”
Section: Introductionmentioning
confidence: 99%